Millennium Dreams: Arts, Culture and Heritage in the Life of Communities - Jeannotte, M. Sharon (Université d'Ottawa | University of Ottawa, 2005)
What kind of culture do citizens value? How do they assess what is a cultural activity and how does this activity fit within the everyday life of communities? To what extent is cultural capital linked with the social capital of the community? This study makes use of the Our Millennium database, which was a special initiative of the Community Foundations of Canada (CFC) to mark the new century, to try to answer these questions. In 1999 and 2000, the CFC invited Canadians to make lasting millennium “gifts” to their communities to make them a better place and to register these gifts on an on-line database. These gifts could be made under 11 self-selected theme areas. An assessment of the Our Millennium initiative by the Caledon Institute of Social Policy remarked upon the disproportionate number of projects that featured various aspects of arts, culture and heritage.This study delves more deeply into the Caledon Insitute’s conclusion and, using a social and cultural capital lens, explores why arts, cultural and heritage projects were so prominent among the millennium gifts registered on the Our Millennium database.
Keywords: Social capital; Cultural capital; Communities